Breaking into the export market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A honey exporter from Zambia explains the ?secrets? for successful marketing: quality, quantity, and reliability. These rules, he says, apply to all kinds of marketing whether for domestic or export markets. He also stresses the importance of having a good relationship with his buyers.